The Influence of Social Capital on Community Self-Efficacy in Facing Tsunamis in Pasiripis Village, Surade Sub-District, Sukabumi District - Sanjaya, Waqid (STIKep PPNI Jawa Barat, 2024)
Aims: The purpose of this study was to determine the simultaneous influence of social capital, trust, networks, and social norms on community self-efficacy in dealing with tsunamis in Pasiripis Village, Surade Subdistrict, Sukabumi District. Methods: This was a correlational study with a cross sectional approach. The population was the community of Pasiripis Village, Surade Subdistrict, Sukabumi District with a sample of 364 people using proportional random sampling technique. The instrument was valid and reliable. Data were collected using questionnaires and statistical analysis using multiple linear regression. Results: The study reveals that social capital, trust, social networks, and norms significantly impact the community's self-efficacy in dealing with tsunamis, with a multivariate contribution of 50.6%. These variables have p-values less than 0.05, indicating their significant influence on the community's resilience in the face of a tsunami. Conclusion: The study reveals that social capital, trust, networks, and social norms significantly impact community self-efficacy in Pasiripis Village, Surade Subdistrict, Sukabumi District, and suggests continuous improvement through regular disaster education and training.